Brothersong - Klune, TJ (Green Creek, 2024)
"In the ruins of Caswell, Maine, Carter Bennett learned the truth of what had been right in front of him the entire time. And then it--he--was gone. Desperate for answers, Carter takes to the road, leaving family and the safety of his pack behind, all in the name of a man he only knows as a feral wolf. But therein lies the danger: wolves are pack animals, and the longer Carter is on his own, the more his mind slips toward the endless void of Omega insanity. But he pushes on, following the trail left by Gavin. Gavin, the son of Robert Livingstone. The half-brother of Gordo Livingstone. What Carter finds will change the course of the wolves forever. Because Gavin's history with the Bennett pack goes back further than anyone knows, a secret kept hidden by Carter's father, Thomas Bennett. And with this knowledge comes a price: the sins of the fathers now rest upon the shoulders of their sons."--